Personnel Management of Administrator and School Effectiveness Under Prachuapkhirikhan Secondary Educational Service Area Office - Yuennan, Worayapak; Asso. Prof. Dr. Sakdipan Tonwimonrat, Asso. Prof. Dr. Sakdipan Tonwimonrat (Journal of Dhamma for Life, 2024)
The purposes of this research were to identify: 1) the personnel management of administrator under Prachuap Khiri Khan secondary educational service area office, 2) the school effectiveness under Prachuap Khiri Khan secondary educational service area office and 3) the relationship between the personnel management of school administrator and school effectiveness under Prachuap Khiri Khan secondary educational service area office. The sample were 16 schools under Prachuap Khiri Khan secondary educational service area office. There were 42 people providing information. The instrument employed for data collection was a questionnaire about the personnel management of administrator and the school effectiveness. The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation and Pearson’ s Product Moment Correlation Coefficient. The research findings were as follows: 1. the personnel management of administrator under Prachuap Khiri Khan secondary educational service area office, as a whole were at the highest level. When considering each aspect, it was found to be at the highest level in 6 aspects and at the high level 1 aspect. The arithmetic mean ranking from the highest to lowest were as follows; 1) workforce planning, 2) promoting professional standards and professional ethics, 3) processing of salary increases, 4) recruitment and appointment, 5) promoting discipline morality and ethics for teachers and educational personnel, 6) development of teachers and personnel in education, operations related to personnel administration must be in accordance with the law and 7) promotion Evaluation of the academic status of teachers and educational personnel. 2. The school effectiveness under under Prachuap Khiri Khan secondary educational service area office, as a whole were at the highest level. When considering each aspect, it was found to be at the highest level in 4 aspects and at the high level 3 aspects. The arithmetic mean ranking from the highest to lowest were as follows; 1) a climate of high expectation, 2) a clear school mission, 3) high time on task, 4) instruction leadership, 5) positive home-school relations, 6) frequent monitoring of student progress and 7) a safe and orderly environment. 3. The relationship between the personnel management of school administrator and school effectiveness under Prachuap Khiri Khan secondary educational service area office as a whole were at .01 level of statistical significance.